The relevance of Tremaine McDowell's "Time and the Colleges" and "The Minnesota Program": Indonesian academics’ commentary on American studies education model - Rifka Pratama; Pramod Kumar Singh; Fajrul Falah; Eko Heriyanto (Scientific English, 2025)
American Studies has historically emphasized interdisciplinary inquiry as a means of integrating cultural, social, and historical perspectives within higher education. One of the foundational contributions to this tradition is Tremaine McDowell’s American Studies (1948), particularly the chapters “Time and the Colleges” and “The Minnesota Program,” which propose the integration of past, present, and future as a core educational principle. This article presents a qualitative conceptual analysis of McDowell’s pedagogical framework, examining its relevance and adaptability within the context of Indonesian American Studies education. Drawing on close textual analysis of McDowell’s writings and selected foundational literature in American Studies, the study identifies key themes including temporal integration, interdisciplinarity, experiential learning, and curriculum flexibility. The findings indicate that McDowell’s framework remains conceptually valuable for promoting holistic learning and interdisciplinary collaboration, while also revealing limitations related to contextual differences between mid-twentieth-century American higher education and contemporary Indonesian academic settings. This study suggests that future research may extend this conceptual analysis through empirical investigation of curriculum implementation, classroom practices, and student learning outcomes, as well as comparative studies across non-Western American Studies programs. Such research would further clarify the applicability of classical American Studies frameworks in diverse educational contexts.